Peripheral Membrane Proteins - Tanabe, Shihori (IntechOpen, 2018)
The peripheral membrane proteins transduce the extracellular signaling into the cells. The peripheral membrane proteins include the G protein-coupled receptors, receptor tyrosine kinases, channels and transporters. The signals, which are transduced via the peripheral membrane proteins, activate several pathways including G protein signaling, MAPK signaling, TNF signaling, TGF? signaling, Wnt signaling and Hedgehog signaling. The peripheral membrane proteins transduce the signaling from the extracellular ligands into the cells. This book intends to provide a comprehensive overview of the features and signaling of peripheral membrane proteins, which includes the molecular structure and interaction. The insights into membrane proteins associated with diseases and therapeutics and the effects of drugs and chemicals are also discussed in this book.